(untitled) (Conference Zone, 2022)
This article describes the results of experiments on the selection of high-quality lines of bread wheat, as well as the yield of bread wheat in the conditions of rainfed areas, and their transfer to the next stages. The experiment used 33 lines and 2 local check varieties created by local hybridization. Yield of bread wheat lines, 1000 grain vans, grain nature and grain quality indicators were selected for the next stages of selection work by selecting lines higher than the local check varieties